Trees and multistorey agriculture in Africa - Dupriez, Hugues; Leneer, Philippe de (Technical Centre for Agricultural and Rural Cooperation, 1998)
Part I deals with the relationship between trees and people, and the threat to trees posed by social, economic and political factors. Part II focuses on multistorey farming, an economically sound cropping method used in many tropical regions. The annexes provide useful tables on food and fodder composition.